Diagnosis of strategy for enforcement of competitiveness of construction enterprises in conditions of sustainable development - Semenov, A. G. (Ways to Improve Construction Efficiency, 2018)
Theoretical approaches to the formation of the concept of "strategic competitiveness of the enterprise" are studied. It is revealed that the main sign of maintaining the competitiveness of the enterprise in the strategic dimension is its ability to maintain a competitive position in the long run. The method of the Boston Consulting Group was used to diagnose the strategic competitiveness of developers in Kyiv.